‘Pathology without Pathos’: Transvaluating Blackness and Metaphors of Disease - Sara-Maria Sorentino (Law Text Culture, 2022)
In this article, I diagnose anti-black determinants that link and delink black populations to the discourse of disease, focusing on the AIDS crisis and epidemiological genealogies of causation. Against the pathologizing of black cultural choices, the liberal-Left has disaggregated the conjunction of blackness with disease. In implying an extra-social element to race, however, such a strategy runs the risk of conceptually and politically removing race from the conditions of its emergence: the violent global abstractive forces of slavery that experimentally deployed blackness as disease, infection, virus, risk, and contaminant in the first instance. Drawing from Saidiya Hartman’s theorization of ‘fungibility’ and Sylvia Wynter’s reading of ‘bios’, I propose an alternative to de-pathologizing. If race does not precede its cohabitation with slavery’s herculean experiment in human sorting, then a more explanatory starting point might be forged by diagnosing the circular causal mechanisms by which blackness causes its own pathology. I close with a call to explore ways the disease metaphor has been activated for black revolutionary struggle—how slavery’s biological experiment in controlling human reproduction (life, death, and sexuality) is always also turned against its founding violence as an emancipatory biological weapon.